Learn Multiply A2 Minus B2 A2 Plus B2

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Multiply: (a² - b²), (a² + b²)

**Solution:**

Given, __multiply__ (a² - b²), (a² + b²)

Using the __standard identity__ (x + y)(x - y) =x² - y²

Here, x = a² and y = b²

⇒ (a² - b²) × (a² + b²)

= [(a²)² - (b²)²]

= a⁴ - b⁴

**✦ Try This: **Multiply: (p³ - q³), (p³ + q³)

Given, Multiply: (p³ - q³), (p³ + q³)

Using the standard identity (x + y)(x - y) =x² - y²

Here, x = p³ and y = q³

⇒(p³ - q³) x (p³ + q³)

= [(p³)]² - [(q³)]² = p⁶ - q⁶

**☛ Also Check: **NCERT Solutions for Class 8 Maths Chapter 9

**NCERT Exemplar Class 8 Maths Chapter 7 Problem 83(xv)**

## Multiply: (a² - b²), (a² + b²)

**Summary:**

Multiplying (a² - b²), (a² + b²) we get, a⁴ - b⁴

**☛ Related Questions:**

Math worksheets and

visual curriculum

visual curriculum